Pengaruh Promosi Dan Harga Terhadap Keputusan Pembelian Kartu SIM IM3 Pada Masyarakat Kota Maumere - Hilmiyadin, Rizqi Brian; Rengga, Andreas; Realino, Dimas; Muga, Richardus (Jurnal Projemen UNIPA, 2026)
This study aims to analyze the effect of promotion and price on the purchase decision of IM3 SIM cards among the people of Maumere City. The study uses a quantitative method with a causal associative approach. Data was obtained through the distribution of questionnaires to respondents who use IM3 SIM cards, with a Likert scale instrument. Data analysis was carried out using multiple linear regression. The results of the study indicate that partially, promotion has a significant effect on purchase decisions, as does price, which is also proven to have a significant effect. Simultaneously, promotion and price have a significant effect on purchase decisions, with a coefficient of determination (R²) of 0.986. This means that 98.6% of the variation in purchase decisions is influenced by promotion and price, while the remaining 1.4% is influenced by other factors outside this study. These findings indicate that appropriate promotional strategies and proper pricing play an important role in enhancing consumer purchase decisions. The research results are expected to provide input for companies, particularly telecommunications service providers, to develop more effective marketing strategies.